2004
DOI: 10.1016/j.jacc.2004.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of thiobarbituric acid reactive substances predict cardiovascular events in patients with stable coronary artery disease

Abstract: Serum levels of TBARS were strongly predictive of cardiovascular events in patients with stable CAD, independently of traditional risk factors and inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 43 publications
10
139
0
6
Order By: Relevance
“…Walter and colleagues demonstrated that serum oxidative stress markers such as thiobarbituric acidreactive substances are predictive of cardiovascular events including fatal and nonfatal myocardial infarction. (21) Oxidative stress is also associated with a faster bone turnover, higher bone resorption, and osteoporosis because oxidative stress inhibits osteoblastogenesis. (22) Recently, a study demonstrated that oxidative stress was increased in older patients with hip fracture compared with healthy elderly controls.…”
Section: Discussionmentioning
confidence: 99%
“…Walter and colleagues demonstrated that serum oxidative stress markers such as thiobarbituric acidreactive substances are predictive of cardiovascular events including fatal and nonfatal myocardial infarction. (21) Oxidative stress is also associated with a faster bone turnover, higher bone resorption, and osteoporosis because oxidative stress inhibits osteoblastogenesis. (22) Recently, a study demonstrated that oxidative stress was increased in older patients with hip fracture compared with healthy elderly controls.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Biomarkers of oxidative stress, such as serum malondialdehyde level measured as thiobarbituric acid-reactive substances, oxidized low-density lipoprotein, oxidation injury of DNA, 8-hydroxydeoxyguanosine and urinary excretion of 8-iso-prostaglandin-F2a, are generally measured in laboratories. [4][5][6][7] On the other hand, as indices of antioxidant potential, intracellular levels of superoxide dismutase and glutathione peroxidase have mainly been measured. [8][9] However, these assay methods are complex and are not suitable for analysis of a large number of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, earlier studies have also revealed an increase in lipid peroxidation, a type of free radical process, in patients with type II hypercholesterolemia [3]. Marinez-Sanches et al [18] note increased concentrations of MDA (malondialdehyde), the main end-product of lipid peroxidation, in patients with hypercholesterolemia, while Walter et al [19] demonstrate a correlation between the concentration of TBARS and the incidence of cardiovascular events. Uydu et al [20] report similar results following the use of atorvastatin in patients with hypercholesterolemia or hyperlipidemia: a decrease in the concentration of TBARS was seen after 12-week therapy at a dose of 10 mg/day.…”
Section: Discussionmentioning
confidence: 97%